Fundoplication versus post-operative medication for gastro-oesophageal reflux in children with neurological impairment undergoing gastrostomy. - Vernon-Roberts, A; Sullivan, P (2007)
BACKGROUND: Children with neurological impairments (NI) frequently experience feeding difficulties which can lead to malnutrition and growth failure. Gastrostomy feeding is now the preferred method of providing nutritional support to children with NI who are unable to feed adequately by mouth. Complications may arise as a result of gastrostomy placement and the development or worsening of gastro-oesophageal reflux (GOR) has been widely reported. This has led to the frequent use of surgical anti-reflux treatment in the form of a fundoplication, or other Anti-Reflux Procedures. Fundoplication is associated with a high recurrence rate, surgical failure and significant morbidity and mortality. Since Proton Pump Inhibitors (PPIs) were introduced in the 1990s they have come to play a larger part in the medical management of GOR in children with NI. Uncontrolled studies suggest that PPIs may be a safe, appropriate treatment for GOR. Other agents currently used include milk thickeners, acid suppression drugs, acid buffering agents, gut motility stimulants and sodium alginate preparations. There are risks and benefits associated with both surgical and medical interventions and further comparison is necessary to determine the optimal treatment choice. OBJECTIVES: To compare the effectiveness of anti-reflux surgery and anti-reflux medications for children with NI and GOR who are undergoing placement of a gastrostomy feeding tube. SEARCH STRATEGY: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) up to Issue 2, 2006, MEDLINE (1966 to June 2006), EMBASE (1980 to week 33, 2006), CINAHL (1982 -to May, week 4, 2006), LILACS (1982 to June 2006), ISI Web of Science (1970 to June 2006) and the Child Health Library (searched June 2006). We also performed online searches of trial registries, medical journals, conference proceedings, dissertations and theses. Specialists in the medical and industry setting were contacted for knowledge of completed or ongoing trials. SELECTION CRITERIA: We sought to include only randomised controlled trials that recruited children up to the age of 18 years with NI and GOR who were undergoing gastrostomy tube insertion. DATA COLLECTION AND ANALYSIS: Two reviewers worked independently on selected trials and performed data extraction and assessment of trial quality. MAIN RESULTS: No trials were identified that satisfied the criteria for this review. AUTHORS' CONCLUSIONS: There remains considerable uncertainty regarding the optimal treatment when faced with the decision of fundoplication surgery versus anti-reflux medications for gastro-oesophageal-reflux in the child with neurological impairment who is undergoing gastrostomy insertion. There is a need for robust scientific evidence in order to provide data on the comparable risks or benefits of the two interventions.